2022
DOI: 10.1002/ccd.30182
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in transcatheter aortic valve replacement use and outcomes by race, ethnicity, and sex

Abstract: Objectives: To identify trends in transcatheter aortic valve replacement (TAVR) use and outcomes by race (non-Hispanic White, Black), ethnicity (Hispanic), and sex over time.Background: Despite rapid growth in TAVR use over time, our understanding of its use and outcomes among males and females of underrepresented racial/ethnic groups remains limited.Methods: A retrospective analysis of hospitalizations from 2013 to 2017 from the Healthcare Cost and Utilization Project database was performed.Results: White pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…and bariatric surgery use are similar to others’ within VA (13,17). Our analysis does not extend to more novel surgical or endoscopic interventions, however given data suggesting late adoption of novel therapies among minoritized individuals (21,50), we expect this information would only exacerbate the severity of inequities identified rather than change the findings. Finally, we cannot determine the extent to which whether the differences we see between race/ethnicity groups are attributable to differential treatment preferences by race/ethnicity, or other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and bariatric surgery use are similar to others’ within VA (13,17). Our analysis does not extend to more novel surgical or endoscopic interventions, however given data suggesting late adoption of novel therapies among minoritized individuals (21,50), we expect this information would only exacerbate the severity of inequities identified rather than change the findings. Finally, we cannot determine the extent to which whether the differences we see between race/ethnicity groups are attributable to differential treatment preferences by race/ethnicity, or other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Incretin-based injectable medications join the existing arsenal of evidence-based, guidelinerecommended obesity treatments, including behavioral weight loss programs, older anti-obesity medications, and bariatric surgery (8)(9)(10)(11)(12), all of which were underutilized in the era prior to incretinbased therapy (13)(14)(15)(16)(17)(18)(19). As marginalized populations frequently receive healthcare innovations slower and later than more resource-rich counterparts (20,21)-and given inequities in use of existing obesity treatments (18,19,(22)(23)(24)(25)-it is far from certain that these next-generation medications are diffusing equitably. Indeed, early experiences suggest the opposite (26); however, inequalities are often attributed to insurance coverage or ability to pay.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, racial and ethnic differences are significant in the application and outcomes of aortic valve replacement. [5][6][7][8][9] While some recent studies have identified patient-related factors influencing these disparities, the role of hospital-related factors remains less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Severe symptomatic aortic stenosis is associated with high mortality, which may be prevented by timely valve replacement ( 3 , 4 ). Transcatheter aortic valve replacement (TAVR) is an effective therapy for severe symptomatic aortic stenosis ( 3 , 4 ), however several studies have documented disparities in access to TAVR among different racial and ethnic groups ( 5 , 6 ). Treatment disparities may arise from differences in socioeconomic, cultural, immigration-related, and genetic factors, as well as the conscious or unconscious racial bias of health care providers ( 7 ).…”
Section: Introductionmentioning
confidence: 99%